Book review: New health information literacies - Sundin, Olof (Nordic Journal of Library and Information Studies, 2022)
Book review of Anna-Maija Multas (2022) New health information literacies. A nexus analytical study, Acta universitatis Ouluensis B Humaniora 192, University of Oulu, Oulu